Side Information Mitigation with new Phase Sequence for Hybrid PTS Scheme - Satyavathi, K.; B.Rama Rao, Dr.; ., . (International Journal of Engineering and Technology, 2018)
This paper focus on presenting a new phase sequence based hybrid PTS approach for OFDM systems to mitigate the problem of PAPR without use of side information. The proposed approach is the exponential constant multiplied for each phase vector so that it can accommodate more number of sub carriers. The modified phase vectors are then multiplied to the original phase vectors so as to obtain a modified version of phase vectors that includes an offset. Experimental results shows that the PAPR is reduced about 04~0.8 db when compared against the traditional PTS scheme deployed for Hybrid systems.Â